OSNOVNA OBILJEŽJA KRIVIČNOG POSTUPKA PROTIV PRAVNIH LICA U BOSNI I HERCEGOVINI - Faruk H. Avdić (Revija za kriminologiju i krivično pravo)
The subject of this paper is the analysis of the provisions of the criminal procedural legislation of Bosnia and Herzegovina devoted to the regulation of the criminal proceedings against the legal person. The paper in question has two aims. The first aim is to cast light on the legal standing of the legal person in the criminal proceedings in the event when this subject finds itself in the role of the person against whom the criminal proceedings are being conducted. In that sense, this analysis took into consideration the unity of the criminal proceedings against the natural and the legal person, the jurisdiction as regards the legal person, the right and duties of the representative of the legal persons, the issue of the delivery and the expenses of the representative, as well the right of the legal person to the defense attorney and compulsory measures applicable against the legal persons. In this connection, by virtue of his significance for the exercise of the defense of the legal person, special attention is devoted to the role of representative of the legal person. The second aim consists in consideration of the shortcomings of the regulation of the procedural standing of the legal person subjected to the criminal procedure. The paper employed the normative and the formal dogmatic method in analyzing the particulars of its subject. The paper concluded that the legal regulation of the criminal proceedings against the legal person in Bosnia and Herzegovina is not at a satisfactory level since many issues of special significance are not included in the criminal procedure acts in force.